Influence of coronavirus disease 2019 case surges on prehospital emergency medical service for patients with trauma in Kobe, Japan - Takeshi Nishimura; Masafumi Suga; Satoshi Ishihara; Shinichi Nakayama; Atsunori Nakao; Hiromichi Naito (Acute Medicine & Surgery, 2023)
Aim In the current era of the coronavirus disease 2019 (COVID‐19) pandemic, the responsiveness of emergency medical service (EMS) transport for patients with internal illness is often delayed. However, the influence of the COVID‐19 pandemic on prehospital transport for patients with trauma has not yet been fully elucidated. This study aims to examine the effect of COVID‐19 case surges on EMS transport for patients with trauma during the COVID‐19 states of emergency in Kobe, Japan. Methods EMS data during the states of emergency were compared with those in the 2019 prepandemic period. The incidence of difficulty securing hospital acceptance (four or more calls to medical institutions and ambulance staying at the scene for 30 min or more) was evaluated as a primary outcome. Secondary outcomes were the time spent at the trauma scene and the number of calls requesting hospital acceptance. The time spent at the trauma scene was stratified by trauma severity. Results The incidence of difficulty securing hospital acceptance increased (1.2% versus 3.2%, P < 0.01). Logistic regression analysis revealed that the duration of the states of emergency was associated with difficulty securing hospital acceptance (odds ratio [OR] 2.08, 95% confidence interval 1.77–2.45; P < 0.01). Although the mean time spent at the trauma scene among the less severe, moderately severe, and severe trauma groups was prolonged, the time for the life‐threatening group did not change. The number of request calls increased during the states of emergency. Conclusion Difficulty securing hospital acceptance increased; however, the time spent at the trauma scene did not significantly change for the life‐threatening group.